Characterization of 3 fluoro-4-formylphenylboronic acid molecule with Density Functional Teory - Emine Babur Şaş; Mustafa Kurt (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2018)
The geometric structure of3-fluoro-4-fomylphenylboronic acid (3-4FPBA) molecule were investigated withDFT/B3LYP/6-311++G(d,p) basis set. Specra of the title molecule were observedby FT-IR and FT-Raman spectra. Theoretical wavenumber were calculated also thesame metot and compared experimental wavenumber (FT-IR and FT-Raman) which werein a good agreement with observed ones. Furthermore, electronic structureproperties of in the title molecule such as HOMO-LUMO, Molecular ElectrostaticPotantial (MEP) and Mulliken charges were investigated by TD-DFT method.